Urogenital Schistosomiasis among Primary School Children in Rural Communities in Obudu, Southern Nigeria - Kenneth Opara; Rebecca Akomalafe; Nsima Udoidung; Udeme Afia; Clement Yaro; Bassey Bassey (Global Health and Education Projects, Inc., 2021)
Background: Schistosomiasis is a Neglected Tropical Disease (NTD) that constitutes a public health problem in Sub-Saharan Africa (SSA), including Nigeria. There is need for updated information on the extent of the disease burden at community level to facilitate effective prioritization and monitoring of the disease. Methods: A cross-sectional study was conducted among school-aged children in Obudu Local Government Area (LGA), one of the 18 LGAs in Cross River State, Southern Nigeria. Seven schools from seven communities were randomly selected for this study. A total of 1,113 urine samples obtained from school-aged children were screened for Schistosoma haematobium (S. haematobium) eggs using standard parasitological method of diagnosis. Proteinuria and hematuria were evaluated using reagent test strips. Results: In this study, 153 (13.7%) children were infected with S. haematobium. More males (86 or 14.7%) were infected than females (67 or 12.7%); the differences were not statistically significant. The overall geometric mean intensity of infection was 13.3 eggs/10ml of urine. Females (13.69 eggs/10ml of urine) had the highest intensity of infection than males (12.91eggs/10ml of urine). Prevalence of hematuria was 152 (13.7%) (95% C.I. = 10.649 - 18.751%) while the prevalence of proteinuria was 172 (15.5%) (95% C.I. = 5.162 - 38.712%). Prevalence of infection significantly (p<0.001) varied among the schools from 7.8% to 28.9%. Children aged 5-9 years old had the highest prevalence of infection 46 (17.1%). The prevalence of urogenital schistosomiasis was 28.9%, 20.5% and 13.2%, respectively, among Betukwel, Ibong, and Ohong communities. Conclusion and Global Health Implications: Urinary schistosomiasis is still endemic in Obudu, Southern Nigeria but with decreased prevalence. Public health mitigation efforts such as mass chemotherapy, provision of safe water supply and sanitation facilities are recommended. Furthermore, health education should be encouraged within schools and communities. Key words: • Schistosoma haematobium • Communities • Schools • Neglected tropical diseases • School-aged children • Parasitology • Chemotherapy • Proteinuria • Hematuria • Obudu • Cross River State • Nigeria.   Copyright © 2021 Opara, et al. Published by Global Health and Education Projects, Inc. This is an open-access article distributed under the terms of the Creative Commons Attribution License (CC BY 4.0) which permits unrestricted use, distribution, and reproduction in any medium, provided the original work, first published in this journal, is properly cited.